Pendekatan Pedagogik Guru PAI dalam Menghadapi Tantangan Abad 21 di SDN 162 Warungjambu - Aulia, Sephia Musyaffa Nur; Shendyka, Muhammad; Budiyanti, Nurti (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study aims to examine the challenges and strategies of Islamic Religious Education (PAI) teachers in facing the demands of 21st-century learning in elementary schools. The research focuses on digital literacy constraints, students' social backgrounds, and limited learning facilities that impact the teaching and learning process. The method used was descriptive qualitative with in-depth interviews. The results show that Islamic Religious Education (PAI) teachers employ various strategies, such as lectures, group discussions, and the use of digital media to encourage active student engagement. Furthermore, teachers strive to develop students' potential not only in cognitive aspects but also in character and motivation through their roles as facilitators, innovators, motivators, and character mentors, as well as lifelong learners. Assessments are used to understand individual needs, in accordance with the child's age-related development, which demands different approaches. Despite challenges related to age and limited resources, teachers continue to strive to improve 21st-century competencies through training, independent learning, and technology adaptation. This study emphasizes the importance of supporting facilities and strengthening technology-based training for Islamic Religious Education (PAI) teachers to enable them to deliver learning that is relevant to students' needs in the digital age.